2021
DOI: 10.1016/j.anr.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Anger Management Program for Nurses

Abstract: Purpose: The purpose of this study was to examine the effects of an anger management program on anger, job stress, psychological well-being, and heart rate variability in clinical nurses. Methods: A quasi-experimental study was conducted using a nonequivalent control group, pretesteposttest design Q5 with repeated measures. The participants included 43 nurses assigned to the experimental and control groups. Anger, job stress, psychological well-being, and heart rate variability were evaluated before the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…La razón neurofisiológica (42)(43)(44) del porqué de esta respuesta del cerebro emocional (sistema límbico) se encuentra en la velocidad de conducción nerviosa que se tiene en las conexiones en la interpretación de amenaza en el mundo exterior. En otras palabras, las conexiones del sistema límbico y los órganos de percepción de amenaza son mucho más rápidas y tardan en trasmitirse 125 milisegundos, mientras que la conexiones entre los sistemas sensoriales y la neocorteza tienen una conducción más lenta y tardan 450 milisegundos, es decir, es 3,6 veces más lento en comparación con la conexión de los órganos de los sentidos y el sistema emocional (45)(46)(47)(48) .…”
Section: Curva De Hostilidadunclassified
See 1 more Smart Citation
“…La razón neurofisiológica (42)(43)(44) del porqué de esta respuesta del cerebro emocional (sistema límbico) se encuentra en la velocidad de conducción nerviosa que se tiene en las conexiones en la interpretación de amenaza en el mundo exterior. En otras palabras, las conexiones del sistema límbico y los órganos de percepción de amenaza son mucho más rápidas y tardan en trasmitirse 125 milisegundos, mientras que la conexiones entre los sistemas sensoriales y la neocorteza tienen una conducción más lenta y tardan 450 milisegundos, es decir, es 3,6 veces más lento en comparación con la conexión de los órganos de los sentidos y el sistema emocional (45)(46)(47)(48) .…”
Section: Curva De Hostilidadunclassified
“…Dominar las nociones sobre las etapas de la hostilidad nos brinda la erudición para realizar una intervención de la manera más propicia, oportuna y adecuada, lo cual nos dará mayor probabilidad de éxito ante una situación de conflicto. El entendimiento de los aspectos neurofisiológicos (48) que se originan en el cerebro humano nos dará la paciencia y la elocuencia para acompañar la parte hostil a una fase reconciliadora.…”
Section: Curva De Hostilidadunclassified
“…The main finding of the current study was that total aggression scores decreased significantly immediately after the training, and the effect remained for 3 months. Among the subscales, the anger and hostil- Previous studies on anger management programmes for nurses reported improved levels of anger (Yun & Yoo, 2021) 2021). Our results are in line with these studies.…”
Section: Changes In Aggression Scores Due To Implementation Of Educat...mentioning
confidence: 99%
“…Our results are in line with these studies. In terms of the duration of the effectiveness, two studies reported continued effectiveness at 4-week postprogramme (Turan, 2021;Yun & Yoo, 2021).…”
Section: Changes In Aggression Scores Due To Implementation Of Educat...mentioning
confidence: 99%
See 1 more Smart Citation